Republic of Congo : 2010 Article IV Consultation and Fourth Review Under the Three-Year Arrangement Under the Extended Credit Facility, and Request for Modification of Performance Criteria-Staff Report; Staff Supplement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Congo. (IMF Staff Country Reports; Country Report ;, 2011)
In this study, economic performance remained robust throughout the global downturn, and shows signs of further strengthening. In 2010, the external position improved significantly, as fiscal surpluses raised official foreign assets, and the Highly Indebted Poor Countries (HIPC) debt relief significantly reduced external liabilities. Macroeconomic stability is well established, and the external position has improved. Private sector development has reduced oil dependence and is assuring sustained poverty-reducing growth. Efforts should be supported by policies to increase the private sector's access to credit, and deepen financial intermediation to improve the financial performance of state-owned enterprises.